Arsitektur Masjid Lima Kaum Batusangkar dan Falsafah Masyarakat Minangkabau - Zainuddin Zainuddin (Jurnal Lektur Keagamaan, 2013)
The architectural model of the ritual place represents the way of life of the society. This study tries to trace back the philosophical meaning of the architecture of Lima Kaum Mosque in Butusangkar, West Sumatera. This study found a relation between the mosque architecture with the philosophy of Minang society. This mosque was built by using 119 poles, which represent the description that the Nagari Lima Kaum has one hundred nineteen leaders, or called as ninik-mamak. Keywords: Lima Kaum Mosque, Architect, Minang Philosophy